Deep Learning Pedagogy, Ethical Awareness, and Critical Digital Literacy in Higher Education: A Systematic Review - David Berthony Manalu; Rudi Hartono; Yuliati (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This systematic literature review examines how deep learning pedagogy influences students’ ethical awareness and critical digital literacy in higher education. Existing research has discussed deep learning, digital literacy, and ethical awareness separately, yet limited attention has been given to how these three constructs intersect as an integrated pedagogical concern in university learning. To address this gap, the review analyzed 16 articles published between 2016 and 2026, selected from Scopus, ERIC, ScienceDirect, SpringerLink, Taylor & Francis Online, and SINTA 1 and 2 journals. The review followed systematic review procedures informed by Zawacki-Richter et al. and PRISMA 2020, with analysis focused on publication trends, countries, research methods, conceptualizations, pedagogical strategies, and research gaps. The findings show that deep learning pedagogy is commonly associated with student-centered learning, higher-order thinking, reflection, problem-solving, and authentic digital inquiry. Its influence is more evident in critical digital literacy than in ethical awareness, although recent AI ethics studies show growing attention to academic integrity, moral sensitivity, and responsible technology use. The novelty of this review lies in synthesizing deep learning pedagogy as a potential pathway for developing ethically aware and critically literate university students in digital higher education